Green Communication in Development of the Ciliwung River School Living Laboratory for Islamic-Based Eco-Tourism for Children in Jakarta - Nada Arina Romli; Dini Safitri; M.Fikri Akbar; Mayang Puti Seruni (Empower : Jurnal Pengembangan Masyarakat Islam, 2026)
The Ciliwung River is a lifeline in Jakarta, a legacy of our ancestors that must be preserved for the benefit of the surrounding community. However, the Ciliwung River faces various problems, including recurring flooding, massive pollution (domestic waste, industrial waste, and microplastics), declining water quality, and land-use changes that worsen hydrological conditions. The Mat Peci community addressed the challenges of Ciliwung River conservation by establishing the Ciliwung River School, utilizing the surrounding area as a living laboratory consisting of a hydroponic garden, a chicken farm, an orchard, a flower garden, a living pharmacy for waste treatment, and the processing of garden produce into traditional foods. However, this living laboratory has not yet received widespread public attention. Therefore, a development model is needed to attract public attention and increase brand awareness. This study aims to develop an appropriate ecotourism model for the Ciliwung River School so that it can develop with islamiv value and become one of the leading Ciliwung River nature conservation areas in Greater Jakarta. This research uses qualitative methods with a case study design. Supported by data collection techniques including semi-structured interviews, the study also conducted passive participant observation and a literature review. Sampling was carried out using the snowball sampling technique with the main theory used being the diffusion of innovation theory. The result oh this study is The result oh this study is Mat Peci Community already designing and implementing three educational living laboratory programs, including communal gardens and gardening classes, circular farming, and a waste bank program. The development of natural laboratories for education has entered the implementation and confirmation phase, in accordance with the diffusion of innovation theory. Al Fikr's concept, which explains how information and skills should be acquired, aligns with the concept of teaching through natural laboratories.